2012
DOI: 10.1007/s00264-012-1587-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful Pavlik treatment in late-diagnosed developmental dysplasia of the hip

Abstract: PurposeThe objective of this study was to evaluate success and complication rates of the Pavlik harness in late-diagnosed hip dislocation (developmental dysplasia of the hip, DDH). We also set out to assess the additional value of an abduction brace for three to six months, when successful reduction using the Pavlik harness was achieved.MethodsWe included 31 patients (31 hips, 28 female, right/left = 4/27) with late-diagnosed hip dislocation treated with a Pavlik harness between 1995 and 2008. The average age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…Increased lateral and superior displacement of the femoral head assessed by quantitative measurements, 29 , 30 complete dislocation of the femoral head (CSHD grade III and IV hips) 12 , 26 , 31 , 44 and an initial acetabular index of more than 36°29 were reported as the radiographic indicators for failure.…”
Section: Results Of Treatmentmentioning
confidence: 99%
“…Increased lateral and superior displacement of the femoral head assessed by quantitative measurements, 29 , 30 complete dislocation of the femoral head (CSHD grade III and IV hips) 12 , 26 , 31 , 44 and an initial acetabular index of more than 36°29 were reported as the radiographic indicators for failure.…”
Section: Results Of Treatmentmentioning
confidence: 99%
“… 17 Although most authors do not recommend the use of the Pavlik harness after 6 mo of age, 18 Pollet et al 19 treated late diagnosed infants between the ages of 6 and 24 mo with a harness claiming encouraging results in Graf type 3 hips but failure in Graf 4 hips. 19 Van de Sande et al 20 reported successful treatment with a Pavlik harness in children between the ages of 5 to 13 mo with better results being achieved in initially less severe dislocated dysplastic hips. 20 The modified Hoffmann-Daimler method used in late-presenting or neglected developmental dysplasia of the hip showed in a series involving 95 hips satisfactory radiographic results in 88 (93%) of the dislocated hips.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Van de Sande et al 20 reported successful treatment with a Pavlik harness in children between the ages of 5 to 13 mo with better results being achieved in initially less severe dislocated dysplastic hips. 20 The modified Hoffmann-Daimler method used in late-presenting or neglected developmental dysplasia of the hip showed in a series involving 95 hips satisfactory radiographic results in 88 (93%) of the dislocated hips. 21 Zionts and MacEwen 22 reported the results in 51 congenitally dislocated hips in 42 children who were between 1 and 3 yr of age at the time of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment of DDH is often successful in infants, it is still a challenge in late-diagnosed DDH [ 7 , 8 ]. Late diagnosis has to be avoided by ultrasound screening in technique described by Graf way [ 9 ]. Muscle contractures around the joint and soft tissue pathology hinder reduction and prevent normal development of the femoral head by inflicting pressure [ 4 ].…”
Section: Introductionmentioning
confidence: 99%